ANALISIS PENGARUH HARGA SAHAM, VOLATILITAS HARGA SAHAM,DAN VOLUME PERDAGANGAN SAHAM TERHADAP BID-ASK SPREAD PERUSAHAAN LQ - 45 (PERIODE 2018 – 2022) - Hernanda, Bima; David Kaluge (Contemporary Studies in Economic, Finance and Banking, 2024)
The researcher aims to identify the impact caused by several factors such as trading volume, stock price volatility, and stock prices on the bid-ask spread in several companies on the LQ-45 index list. A quantitative approach is used as a research method and uses panel data regression analysis. The data used is a time series and cross sectional in the time period 2018 to 2022. Based on the research results, it was found that there was a negative and significant influence between stock prices on the bid-ask spread. Apart from that, it was found that there was a positive and significant influence on the price volatility variable and stock trading volume on the bid-ask spread variable. Overall the bid-ask spread is simultaneously influenced by stock price variables, stock price volatility variables and stock trading volume variables.